PERTANGGUNGJAWABAN PIDANA ANAK DI BAWAH UMUR TERLIBAT TINDAK PIDANA TERORISME - Ramadhan, Azis Akbar; Firdausi, Ulya Shafa; Vanessa, Adinda Rachel (Universitas Muhammadiyah Ponorogo, 2024)
This article which in its writing uses normative research methods, using a statutory approach and a conceptual approach. The formulation of the problem in this research is: 1) What is the criminal responsibility of minors involved in committing criminal acts of terrorism ? 2) What is the legal protection for minors involved in committing criminal acts of terrorism? From the legal research that has been carried out using the research approach mentioned above, it can be concluded that in the first formulation of the problem regarding the criminal responsibility of minors who are involved in committing criminal acts of terrorism, that is, children cannot be held criminally responsible because not all of the conditions for the elements of guilt are met (cumulative). Meanwhile, the second problem formulation discusses the basic considerations for providing legal protection for children and the relevant and appropriate legal protection to be given to children involved as perpetrators of criminal acts of terrorism.